2019
DOI: 10.1080/0092623x.2018.1518886
|View full text |Cite
|
Sign up to set email alerts
|

A Validation Study of the Spanish Version of the Hypersexual Behavior Inventory (HBI): Paper-and-Pencil Versus Online Administration

Abstract: Hypersexuality is a problematic behavior characterized by the combination of an excessive sexual desire and the pathological inability to control it. This study presents the psychometric properties of the Spanish paper-and-pencil and online versions of the Hypersexual Behavior Inventory (HBI), one of the most popular scales to assess this issue. 2250 participants (1070 men) completed a translated version of the HBI (1450 in paper-and-pencil; 800 online). The EFA yielded three factors that explained 67.53% of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 68 publications
1
15
0
2
Order By: Relevance
“…Subsequently, Ballester-Arnal et al. ( in press ) obtained a similar factorial structure (three first-order factors grouped under a second-order factor) through a CFA in a sample of 2,250 participants between 18 and 40 years old, also demonstrating that the HBI is equally applicable in men and women without changes in its factorial structure (metric and configural invariance). In the Spanish validation study, the authors reported an internal consistency of between .82 and .93 for the total score and the subscales.…”
Section: Methodsmentioning
confidence: 81%
“…Subsequently, Ballester-Arnal et al. ( in press ) obtained a similar factorial structure (three first-order factors grouped under a second-order factor) through a CFA in a sample of 2,250 participants between 18 and 40 years old, also demonstrating that the HBI is equally applicable in men and women without changes in its factorial structure (metric and configural invariance). In the Spanish validation study, the authors reported an internal consistency of between .82 and .93 for the total score and the subscales.…”
Section: Methodsmentioning
confidence: 81%
“…Some existing measures also seem particularly well-poised for such evaluation. The widely used HBI-19 has been extensively tested in both clinical and non-clinical populations and translated into several languages for administration (Ballester-Arnal et al, 2019;. Similarly, the Brief Pornography Screen has been tested in nationally representative samples in both the United States and Poland , as well as in treatment seeking samples in Poland and in clinical samples in the United States .…”
Section: Research Implicationsmentioning
confidence: 99%
“…CSBD signs and symptoms were assessed through a new composite index based in three previously validated scales: the Hypersexual Behavior Inventory (HBI, Ballester-Arnal et al, 2019;Reid et al, 2011), the Sexual Compulsivity Scale (SCS, Ballester-Arnal et al, 2013;Kalichman & Rompa, 1995), and the Sexual Addiction Screening Test (SAST, Castro-Calvo et al, 2018;Carnes, 1983). Independently, these measures tend to be excessively narrow in the assessment of CSBD symptoms, not covering the wide range of criteria that should be explored to accurately assess this clinical condition (Womack et al, 2013); however, altogether these scales offer a comprehensive assessment of CSBD symptoms and severity.…”
Section: Composite Index Of Csbd Symptomsmentioning
confidence: 99%